2005
DOI: 10.1159/000083496
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and Nonneuronal Quantitative BACE Immunocytochemical Expression in the Entorhinohippocampal and Frontal Regions in Alzheimer’s Disease

Abstract: In this study, we quantitatively investigated the expression of β-site amyloid precursor protein cleaving enzyme (BACE) in the entorhinohippocampal and frontal cortex of Alzheimer’s disease (AD) and old control subjects. The semiquantitative estimation indicated that the intensity of BACE overall immunoreactivity did not differ significantly between AD and controls, but that a significantly stronger staining was observed in the hippocampal regions CA3–4 compared to other regions in both AD patients and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 93 publications
2
33
0
Order By: Relevance
“…BACE1/␤-secretase can become expressed in both cell types (32,(35)(36)(37), and increased BACE1 expression can be observed in neurons and glia in AD patients and in AD mouse models (35,(37)(38)(39). Although neurons and glia can theoretically contribute to A␤ load in the brain, further work is now needed to address the cell-type specificity of the observed effects of miR-29a/b-1 on BACE1 expression in vivo.…”
Section: Figmentioning
confidence: 99%
“…BACE1/␤-secretase can become expressed in both cell types (32,(35)(36)(37), and increased BACE1 expression can be observed in neurons and glia in AD patients and in AD mouse models (35,(37)(38)(39). Although neurons and glia can theoretically contribute to A␤ load in the brain, further work is now needed to address the cell-type specificity of the observed effects of miR-29a/b-1 on BACE1 expression in vivo.…”
Section: Figmentioning
confidence: 99%
“…The mossy fiber staining pattern for BACE1 was similar to that reported by Laird et al (2005), who used a rabbit antibody against amino acids 46 -163 of BACE1 (Cai et al, 2001). Other groups have also reported cerebral BACE1 immunolocalization in normal and AD humans, as well as in wild-type and APP transgenic mice (Hussain et al, 1999;Rossner et al, 2001;Fukumoto et al, 2002;Sun et al, 2002;Hartlage-Rubsamen et al, 2003;Heneka et al, 2005;Leuba et al, 2005;Singer et al, 2005;Harada et al, 2006). However, a consensus BACE1 immunostaining pattern has not emerged.…”
Section: Bace1 Localization In Brainmentioning
confidence: 99%
“…Previous BACE1 immunolocalization studies in AD lacked consistency, variously reporting BACE1 in neuron cell bodies (Fukumoto et al, 2002;Sun et al, 2002), neurites (Sheng et al, 2003), tangle-bearing neurons (Leuba et al, 2005), and astrocytes around plaques (Rossner et al, 2001;Heneka et al, 2005). We found that typical BACE1 antibodies produce nonspecific backgrounds in immunohistochemistry and bind to numerous non-BACE1 polypeptides on immunoblots.…”
Section: Introductionmentioning
confidence: 99%
“…74 However, in both autoptic AD cases and transgenic mice, BACE1 expression and Aβ deposits are not only restricted to neurons, but they co-localize also with astroglial markers. [77][78][79][80] This suggests that astrocytes may contribute to the generation of pathological protein aggregates in vivo. In keeping, recent studies in vitro confirmed that, under normal conditions, astrocytes possess the APP-processing machinery for generating Aβ peptide, i.e., APP itself, BACE1 and/or its close homolog BACE2.…”
Section: Alzheimer Diseasementioning
confidence: 99%